Evaluating the effect of wind turbine faults on power using the Monte Carlo method - Dariush Biazar; Hamid Khaloozadeh; Mehdi Siahi (Wind Energy, 2022)
Abstract Component damage and failure in sensor or actuator will cause system faults, resulting in reduced or lost performance. This topic has become an interesting and challenging issue that if we know the effect of faults on variables, control schemes can be designed to reduce the effect of faults on the system. Therefore, the quantification of the effect of the faults is very valuable in improving the performance of wind turbines. In this paper, the effect of some important faults is investigated in the three parts: rotor, drive, and power on the output power and the measured variables of wind turbines in the partial and full load regions using the Monte Carlo method. Then, the severity of these faults on the output power is ranked in the two regions by importance factor (IF). Also, due to the fact that some faults cause structural stress due to severe changes in the angle of the blades or their asymmetry, so the stresses caused by faults are discussed. The results show that these faults severity on the output power and the measured variables of wind turbines is different in the two regions. Our conclusion provides an opportunity for wind power plant operators and investors to improve plant performance and scheduled repairs by knowing the effect of faults on wind turbine variables. Knowing effect of the faults or the severity of each of them can increase the operating time of the wind turbine and reduce costs.